The Impact of Exports and Currency Value on Indonesia's Economic Development Before and During Covid-19 Period 2011-2023 - Yusuf, Dira Maulana; Apriliana, Tria (Ekonomis: Journal of Economics and Business, 2025)
The COVID-19 pandemic significantly impacted global economies, including Indonesia. This study aims to analyze the effects of exports and exchange rates on Indonesia’s economic development during 2011-2023. Using a quantitative approach with the Two-Stage Least Squares (2SLS) method, the results indicate that exports positively contributed to economic growth before the pandemic. However, this contribution weakened during the pandemic due to global supply chain disruptions. Exchange rate depreciation had a positive impact on export competitiveness before the pandemic, while its influence became insignificant during the pandemic. Inflation consistently showed a negative impact on economic growth throughout the study period. This research highlights the importance of export diversification, exchange rate stability, and inflation control as strategies to support sustainable economic growth.